1968
DOI: 10.2307/2528465
|View full text |Cite
|
Sign up to set email alerts
|

Line Transect Method of Estimating Grouse Population Densities

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. International Biometric Society is collaborating with JSTOR to digitize, preserve and extend access to Biometrics. SUMMARYA new estimator is proposed for estimating ruffed gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 9 publications
0
38
0
3
Order By: Relevance
“…The Betsiboka-Ikopa region remains to be more carefully surveyed in order to determine if the species was ever or is still present. Meyers and Ratsirarson, (1989) LT-DS: Line transect-distance sampling; Field method: Müller (Müller et al 2002); CDS: Conventional Distance Sampling (Buckland et al 2001);Whitesides (Whitesides, 1988); MPD: Mean Perpendicular Distance (Gates et al 1968). Table 6: Conservation status update for crowned sifaka (Propithecus coronatus).…”
Section: Population Density and Sizementioning
confidence: 99%
“…The Betsiboka-Ikopa region remains to be more carefully surveyed in order to determine if the species was ever or is still present. Meyers and Ratsirarson, (1989) LT-DS: Line transect-distance sampling; Field method: Müller (Müller et al 2002); CDS: Conventional Distance Sampling (Buckland et al 2001);Whitesides (Whitesides, 1988); MPD: Mean Perpendicular Distance (Gates et al 1968). Table 6: Conservation status update for crowned sifaka (Propithecus coronatus).…”
Section: Population Density and Sizementioning
confidence: 99%
“…The negative exponential model and the half normal model are the most prominent models. Gates et al (1968) suggested the negative exponential model with detection function, The corresponding pdf is,…”
Section: Some Parametric Estimatorsmentioning
confidence: 99%
“…As an illustration we reexamine the data on ruffed grouse from the Cloquet Forest Research Center that were first discussed in the statistical literature by GATES et al (1968). These authors commented that one reason for the failure of the data to follow a Poisson distribution could be the tendency of the birds to flush in pairs.…”
Section: The Ruffed Grouse Datamentioning
confidence: 99%